Determination of School-Related Problems in Children Treated for Cancer. (October 2014) - Yilmaz, Medine C.; Sari, Hatice Yildirim; Cetingul, Nazan; Kantar, Mehmet; Erermis, Serpil; Aksoylar, Serap
This descriptive and case–control study was carried out in a pediatric oncology outpatient clinic to determine the school-related physical, social, and psychological problems and problems experienced in academic achievement of children treated for cancer. The sample of the study consisted of 56 Turkish patients with cancer, aged 7–18 years, who were in remission and attending school as well as their parents, a control group of patients who did not have cancer, and their teachers. A Child Information Form, a Child Health Questionnaire Parent's Form of 50 questions, a Behavior Evaluation Scale for Children, and Young People and a Teacher's Report Form were used as data collection tools in the study. Of the children, 30.3% experienced various physical difficulties stemming from cancer therapy that affected their school life. The number of late enrollments, the number of children repeating a grade, and the rates of school absenteeism were also found to be higher in the survivors than in the controls.